Alexithymia, resilience, somatic sensations and their relationships with suicide ideation in drug naïve patients with first‐episode major depression: An exploratory study in the "real world" everyday clinical practice. Issue 3 (11th August 2019) - De Berardis, Domenico; Fornaro, Michele; Valchera, Alessandro; Rapini, Gabriella; Di Natale, Serena; De Lauretis, Ida; Serroni, Nicola; Orsolini, Laura; Tomasetti, Carmine; Bustini, Massimiliano; Carano, Alessandro; Vellante, Federica; et al.
Abstract: Aim: The present study is aimed at revaluating alexithymia, somatic sensations, resilience and their relationships with suicide ideation in drug naïve adult outpatients suffering from first episode major depression (MD). Methods: Data of 103 adult outpatients (49 men, 56 women) with a diagnostic and statistical manual of mental disorders, 4th edition, text revision (DSM‐IV‐TR) diagnosis of MD were analysed. Alexithymia was measured using the 20‐item Toronto Alexithymia Scale (TAS‐20) and resilience with the 25 items Connor‐Davidson Resilience Scale (CD‐RISC) whereas depression was evaluated using the 17‐item Hamilton Depression Rating Scale, somatic sensations with the Body Sensations Questionnaire and suicide ideation with Scale of Suicide Ideation (SSI). Results: Gender comparisons between all demographic and clinical variables showed no significant differences in all variables. Subjects who were found positive for alexithymia showed higher scores on all clinical variables controlling for age, gender and duration of the current episode. In a linear regression model, lower scores on CD‐RISC and Difficulty in Identifying Feelings dimension of TAS‐20 were significantly predictive of higher scores on SSI. Conclusions: Alexithymia and low resilience were significant predictors of increased suicide ideation in a first MD episode. However, study limitations must be considered and future research needs are being discussed.